Implication sémantique des prédicats dans la grammaire à base sémantique de Stanisław Karolak - Śmigielska, Beata (Neophilologica, 2019)
The following paper discusses the problem of the semantic implication of predicates based on Stanisław Karolak’s theory of semantics-based grammar. As the notion of predicate-argument structure is fundamental for this theory, it is crucial to establish the number and type of arguments assigned to a given predicate. The process of assigning the appropriate number of argument positions opened by a predicate and argument-adjunct distinction is a complex and not always clear procedure. Taking into consideration the notions, definitions and propositions resulting from the theory at hand here, the author carries out an analysis of the selected group of predicates that, taking this point of view, may seem to be problematic.